Una propuesta metodológica para valoración de bienes inmuebles en aplicaciones catastrales (ING) - Castro Fernández, Jorge (2004)
This paper reveals an analisis and proposes for the right application of technical norms for value or real states in municipal applications to comply with what it is established in the Law of property taxation N°7509 and their updates. In order, to do so, the technical norms are defined, their best ways and inconvenients, and it suggests how to improve them. It also suggest how to get value maps by square meter of terrain, their application and methodology for the best way to get them. An estimation of the work times with the suggested methodology, in order to reduce costs, increase performance and get the correct and effective way for making massive property valuation to achieve an increase of the municipal rate basis, is introduced. With the proposed methodology we pretend the Municipality to become effective in increasing the property taxing value, with the subsequent increasing of economic resources. The methodology takes into account some advantages that allow the Municipality to check the established value homogenous value zones for square meter of terrain. This, in order to have an internal control for construction permmission of urbanistic projects, and getting minimum rates by person and activities for the value processing.